Effect of pH and Incubation Time on Dissolved Nitrogen During Autolityc Degradation of Chicken Intestine - Aulia, Eldiani; Sjaifullah, Achmad; Handayani, Wuryanti; Busroni; Oktavianawati , Ika; Reza, Muhammad (Department of Chemistry, Faculty of Mathematics and Natural Sciences, University of Jember, 2023)
Chicken intestine is a part of internal organs, which are rich in protein and protease enzymes. The protease enzyme could self-degrade (autolytic degradation process) proteins in the chicken intestine at an appropriate pH and incubation time. This process produces a shorter chain polypeptide having a higher solubility protein called protein hydrolysates. Protein hydrolysates have shown a good impact in foods and health applications. In this study, the autolytic degradation of chicken intestine was carried out to obtain protein hydrolysates. The effect of pH and incubation time on the dissolved nitrogen (%N) and protein content ([protein]) in hydrolysate from the autolytic degradation of chicken intestine explained in this paper. The incubation pH used in this study was 2.5, 3.5, 5.5., and 6.3 while the the incubation time was 0, 6, 12, and 18 h. Chicken intestine was incubated for 18 h at several different pHs, and the % N and protein content were determined by using Formol titration and Bradford methods, respectively, within 6 h intervals. It was obtained the % N and [protein] content increase at pH 2.5 and 3.5 during 18 h of incubation time and they were decreased at a higher pH. The optimum % N and [protein] content were 5.98±0.51 % and 25.3±0.04 mg mL-1, respectively, obtained at pH of 2.5 during 18 h incubation time.